PEMBELAJARAN PENGENALAN KOMPUTER DI TAMAN KANAK-KANAK ISLAM AL AZHAR 21 PONTIANAK TENGGARA - Pangestu Putri, Ayu Aprilia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractLearning of introduction to computer is an effort to improve the quality of learning. The main learning activity for infants is to play and any kind of activity which bears fun to them. Therefore, in learning of introduction to computer for children shall be appliied in fun ways of teaching so that they may feel pleased and not under pressure. The facility and human resource in learning of introduction to computer also might be a problem in learning procurement of introduction to to computer in preschool. By that reason, the researcher aims to research about learning of introduction to computer especially in Al-Azhar 21 Kindergarten of South East Pontianak. The data is resourced of interview result with the head of the Kindergarten, computer teacher, observation in teacher's activity during the learning of introduction to computer and documentary. The result of this research describes the learning formation of introduction to computer that is made as learning material to the children. The method of study that is used by the teacher to teach the computer specifically in kindergarten.Â And the obstacle that is faced rhe kindergarten in during teaching the introduction to computer.Keyword: learning of introduction to computer to children